Optimization of Low‐Dimensional Components of Quasi‐2D Perovskite Films for Deep‐Blue Light‐Emitting Diodes - Yuan, Shuai; Wang, Zhao‐Kui; Xiao, Lei‐Xin; Zhang, Chun‐Feng; Yang, Sheng‐Yi; Chen, Bing‐Bing; Ge, Hui‐Ting; Tian, Qi‐Sheng; Jin, Yan; Liao, Liang‐Sheng (Advanced materials (Weinheim), 2019)
Compared to efficient green and near‐infrared light‐emitting diodes (LEDs), less progress has been made on deep‐blue perovskite LEDs. They suffer from inefficient domain [various number of PbX6− layers (n)] control, resulting in a series of unfavorable issues such as unstable color, multipeak profile, and poor fluorescence yield. Here, a strategy involving a delicate spacer modulation for quasi‐2D perovskite films via an introduction of aromatic polyamine molecules into the perovskite precursor is reported. With low‐dimensional component engineering, the n1 domain, which shows nonradiative recombination and retarded exciton transfer, is significantly suppressed. Also, the n3 domain, which represents the population of emission species, is remarkably increased. The optimized quasi‐2D perovskite film presents blue emission from the n3 domain (peak at 465 nm) with a photoluminescence quantum yield (PLQY) as high as 77%. It enables the corresponding perovskite LEDs to deliver stable deep‐blue emission (CIE (0.145, 0.05)) with an external quantum efficiency (EQE) of 2.6%. The findings in this work provide further understanding on the structural and emission properties of quasi‐2D perovskites, which pave a new route to design deep‐blue‐emissive perovskite materials. A quasi‐two‐dimensional perovskite film with stable domain distribution is prepared based on a new spacer. The film containing pure bromide perovskite exhibits enhanced deep‐blue fluorescence with quantum yield of 77% by low‐dimensional component engineering. As a result, the corresponding light‐emitting diodes deliver stable deep‐blue emission with a peak external quantum efficiency of 2.6%.